Islamic ethics and character building - Abdullah, Fatimah (IIUM Press, 2014)
The present book attempts to present Islamic ethics first from its multifaceted nature; ethics as akhlaq is presented from the psychological, educational and spiritual aspects and every bit of character building or ethic is supported by pertinent verses of the Holy Qur'an, the stories of the Prophets and the sirah and shama'il of our beloved Prophet Muhammad (PBUH). Second, an effort is made to present Islamic ethics from the practical and modern angles. To enliven the discipline we have relied on Tasawwuf area that have been neglected by earlier researchers. In fact most of the early sufi scholars such as al-Ghazali, al-Mu'asibi and al-Balkhi were Islamic psychologists who did their best to spiritually invigorate their disciples and refine their character. This approach of Sufi ethics or Tasawwuf with its self-introspection in nature will serve as underpinning of individual and societal wellbeing and mental health that conditioned the development and prosperity of the ummah.